MODALITAS PEMBEDAHAN EPILEPSI INTRAKTABEL PADA ANAK - Prastiya Indra Gunawan,* Wihasto Suryaningtyas,** Darto Saharso* (NEURONA, 2015)
INTRODUCTION SURGERY IS CONSIDERED TO BE THE TREATMENTOF CHOICE FOR PEDIATRIC CASES OF INTRACTABLE EPILEPSY WHOSERESPONSE TO ORAL ANTIEPILEPSY AGENTS IS INADEQUATE SURGERY FOR INTRACTABLE EPILEPSY IN CHILDREN IS DIFFERENT COMPARED TO ADULTS